2009
DOI: 10.3844/ajeassp.2009.438.445
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of High Voltage Polymeric Insulators in Arid Desert's Simulated Environmental Conditions

Abstract: Problem statement: High Voltage (HV) polymeric insulators are replacing ceramic insulator commonly used for HV outdoor networks due to their ease of handling, reliability and cost. However, their long term performance and reliability are major concerns to power utilities. Approach: To investigate their performance in arid desert's conditions, two types of HV composite insulators were aged as per International Electrochemical Commission (IEC) standard-61109. Additional test samples were subjected to accelerated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…When the age is longer, the larger of will be acquired. This has been acknowledged by Khan [10] in his study using the new samples in which it can be observed that the nature of surface insulator much smoother, homogenous and minimal porous surface as compared to the aged insulators. Meanwhile, related to the environmental stress effect, the condition of will be getting severe when the stresses themselves are worst.…”
Section: Factors Of the Insulator Age And Environmental Stress That A...mentioning
confidence: 87%
“…When the age is longer, the larger of will be acquired. This has been acknowledged by Khan [10] in his study using the new samples in which it can be observed that the nature of surface insulator much smoother, homogenous and minimal porous surface as compared to the aged insulators. Meanwhile, related to the environmental stress effect, the condition of will be getting severe when the stresses themselves are worst.…”
Section: Factors Of the Insulator Age And Environmental Stress That A...mentioning
confidence: 87%
“…Significantly, considering the identical environmental stress, the higher age of service insulator, the larger Ra and porosity of surface insulator will be appeared [13], [19]. This can be described through the loss of the polymer outer layer on the surface, in which it will look like the surface finish of the molding process.…”
Section: Relationship Of Ra With Insulator Age and Environmental Stressmentioning
confidence: 99%
“…Meanwhile, the condition of Ra will be severe due to the high stress environment regardless of how long it has been employed in the service. The accumulated pollution and dust have contributed to influencing the surface roughness of the insulation, thereby reducing the dielectric performance after a long period of time [13]. This is to be observed with the existence of LC on the surface of EPDM and silicon rubber (SiR) as pollution is not fully removed, even after continuous rain [20].…”
Section: Relationship Of Ra With Insulator Age and Environmental Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, studies have also been made on the multi‐stress degradation of polymeric insulators under dry conditions (UV and temperature) to simulate the arid desert and tropical weathering conditions [13–15]. Khan et al [16] simulated the arid desert weathering conditions to investigate the surface hydrophobicity variations of EPDM and SR insulators.…”
Section: Introductionmentioning
confidence: 99%